THE NIGERIAN-BIAFRA WAR: DISSATISFACTIONS, DESTRUCTION AND THE ENGAGING PHILOSOPHIES - Mbarah, George; Ezenwankor, John (African Journal of Social and Behavioural Sciences, 2023)
In this paper, we argue that the avoidable Nigerian-Biafran war of 1967-1970 was unnecessary. This is because the level of dissatisfaction and destruction of lives and property on both warring sides is still hurting the development and unity of modern Nigeria. However, it is incontrovertible that modern Nigeria came into being as a result of the amalgamation of the Northern and Southern Protectorates by Lord E.D. Lugard in 1914, without laying any solid foundation for the political unity of the heterogeneous Nigerian society. The roots of the Nigerian Civil War can be located in the colonial period involving the policies of the British colonial authorities as well the roles played by the Nigerian nationalists, politicians and the military in the immediate pre and post-independence eras of Nigerian history. Therefore, we argue that a non-violent approach is recommended in dispute resolutions. According to Mahatma Gandhi, in resolving disputes and disagreements, it is needless to apply violence instead of dialogue. Nigeria as a multi-ethnic and socio-cultural entity should learn to tolerate each other and whereby their differences could not improve their unity, a non-violent approach becomes necessary for any group that wants to secede.